Upaya Pencegahan Infeksi Menular Seks Pada Komunitas Men Sex Men melalui Penyuluhan - Dewi Sarah; Ulin Nihayah (Griya Widya: Journal of Sexual and Reproductive Health, 2023)
Background: Male sex workers (MSM) are at high risk of contracting HIV/AIDS due to frequent partner changes and anal sex. MSM is the highest risk factor for new HIV cases in Indonesia. Data of MSM (Gay, Bisexual, and Waria) in PKBI Semarang City, until March 2023 amounted to 3185. Purpose: The purpose of this study was to find out in depth about the counseling of Sexually Transmitted Infections (STIs) Men Sex Men (MSM) at the Indonesian Family Planning Association PKBI Semarang City. Method:  This research is a qualitative research with descriptive approach. Data collection techniques used were observation and interview, then the results of the study were analyzed descriptively. Informants were obtained from 3 MSM informants and 3 informants from the PKBI Semarang City team. Result: The results showed that, First, the good cooperation of the PKBI team and support from the Education Office, Health Office, and also from related institutions resulted in the willingness of MSM to participate in activities both education, socialization and counseling. While the obstacles are the lack of budget availability, and the assumption of people who consider the issue of sexual reproductive health is not important, sensitive issues, and do not want to receive information related to reproductive health. Second, the counseling conducted by PKBI Semarang city so far can be said to be good, the extension workers can provide maximum counseling. So far, the prevention of PKBI Semarang by providing condoms, lubricants, IEC and accompanied by education and socialization activities to increase knowledge about STIs and HIV/AIDS.